ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN METODE MIN-MAX: Array - Siboro, Fernando Rikardo; Nasution, Rini Halila (JiTEKH, 2020)
The research carried out is the analysis of raw material inventory control using the economic order quantity (EOQ) method and the Min-Max method. The EOQ method is a method of reducing production costs to a minimum of raw material supplies. Meanwhile, controlling raw materials using the Min-Max method serves to avoid shortages of raw material inventory that result in losses and determine reorder points. Research and the results of calculations carried out when using the EOQ method in the procurement of raw materials will get cost savings. Where the results of the analysis of the total cost of inventory. (TIC) raw materials for wheat flour for 3 consecutive years (2017-2019) based on the EOQ method experienced savings of up to IDR 4,404,510, analysis of total cost of supplies (TIC) of raw sugar for 3 consecutive years (2017 -2019) based on the EOQ method, experiencing savings of up to Rp. 2,566,065, analysis of the total cost of inventory (TIC) of butter raw materials for 3 consecutive years (2017-2019) is based on the EOQ method experiencing savings of up to Rp. 486,426, while the results Calculation of raw material inventory is done when using the Min-Max method. Wheat flour raw material inventory for 3 consecutive years (2017-2019) min stock 4,629.65 kg and max stock 313,844.64 kg, granulated sugar raw material inventory for 3 consecutive years (2017-2019) min stock 1,250 kg and max stock 2,378.6 kg, and butter raw material stock for 3 consecutive years (2017-2019 min stock 500 kg and max stock 954.64 kg. The total cost of raw material inventory calculated according to EOQ and Min-Max less (economical / economical) than that issued by the company.